Multisite ropivacaine for pain relief after laparoscopic cholecystectomy: a placebo controlled study at a tertiary care teaching hospital - Samal, Debasish; Sahoo, Rashmiranjan; Patra, Kalpita (International Surgery Journal, 2017)
Background: Laparoscopic cholecystectomy has emerged as the gold standard for gallstone diseases. The preference of laparoscopic cholecystectomy (LC) over open cholecystectomy (OC) is because of decreased pain and early discharge. Still pain remains as a major cause of concern. In this current study, we have evaluated the effect of Intraperitoneal instillation of Ropivacaine along with subcutaneous injection around the trocar sites in patients undergoing LC. Methods: In this prospective study two groups of patients were selected 50 patients in each group. Control groups were given 100ml of 0.9% NS and other group received 2mg/kg intraperitoneal ropivacaine 0.25% diluted in 100ml of NS. All the outcome results were documented and analyzed for conclusion. Results: When we compared the pattern of pain in both the groups over the period of 24 hours postoperative, it was revealed that in the group C shoulder pain was seen in 30% of cases, followed by incisional pain in 76%. Right hypochondriac pain was 84% and diffuse abdominal was 82%. In group R they were being 10%, 20%, 32% and 70% respectively. The postoperative rescue analgesia for group C was demanded after around 1 to 2 hours of reaching the ward whereas in the group R it was around 4 hours. Discharge after adequate pain relief was seen early in group R (24 hours) than in the group C (36-48hours). Conclusions: The database of our retrospective study regarding age and sex incidence, clinicopathological features and therapeutic outcome was comparable to other studies in various literatures.